Pengaruh Good Corporate Governance, Corporate Social Responsibility, dan Corporate Financial Performance Terhadap Nilai Perusahan - Hemayani, Ni Made Indah; Dewi, Luh Gede Kusuma (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aimed to determine the effect on good corporate governance, corporate social responsibility, corporate financial performance on firm value. The type of research is quantitative research. The research was used secondary data from the Indonesia Stock Exchange. The population of this research is miscellaneous industry sector companies listed on the Indonesia Stock Exchange in 2015-2019 totaling 44 companies. The sampling technique used purposive sampling. Dependent variable of this research is firm value as measured by Tobin’s Q. Independent variable of this research is good corporate governance which is proxied by corporate secretary, audit committee, and remuneration committee, corporate social responsibility, and corporate financial performance which is proxied by return on assets (ROA). The results of this study showed that (1) corporate secretary had effect on firm value, (2) audit committee had effect on firm value, (3) remuneration committee had effect on firm value, (4) corporate social responsibility had effect on firm value, and return on assets had effect on firm value on miscellaneous industry sector companies listed on the Indonesia Stock Exchange in 2015-2019.